Mononuclear Clusterfullerene Single‐Molecule Magnet Containing Strained Fused‐Pentagons Stabilized by a Nearly Linear Metal Cyanide Cluster. Issue 7 (12th January 2017) - Liu, Fupin; Wang, Song; Gao, Cong‐Li; Deng, Qingming; Zhu, Xianjun; Kostanyan, Aram; Westerström, Rasmus; Jin, Fei; Xie, Su‐Yuan; Popov, Alexey A.; Greber, Thomas; Yang, Shangfeng
Abstract: Fused‐pentagons results in an increase of local steric strain according to the isolated pentagon rule (IPR), and for all reported non‐IPR clusterfullerenes multiple (two or three) metals are required to stabilize the strained fused‐pentagons, making it difficult to access the single‐atom properties. Herein, we report the syntheses and isolations of novel non‐IPR mononuclear clusterfullerenes MNC@C76 (M=Tb, Y), in which one pair of strained fused‐pentagon is stabilized by a mononuclear cluster. The molecular structures of MNC@C76 (M=Tb, Y) were determined unambiguously by single‐crystal X‐ray diffraction, featuring a non‐IPR C 2 v (19138)‐C76 cage entrapping a nearly linear MNC cluster, which is remarkably different from the triangular MNC cluster within the reported analogous clusterfullerenes based on IPR‐obeying C82 cages. The TbNC@C76 molecule is found to be a field‐induced single‐molecule magnet (SMM). Abstract : Fused box : Mononuclear clusterfullerenes MNC@C76 (M=Tb, Y) which do not obey the isolated‐pentagon rule (IPR) contain one pair of fused‐pentagons stabilized by a nearly linear mononuclear cyanide cluster. This situation contrasts with the triangular MNC clusters within the analogous clusterfullerenes of IPR‐obeying C82 cages. TbNC@C76 is identified to be a field‐induced single‐molecule magnet (SMM).